The art of oddworld inhabitants : the first ten years 1994-2004. - Johnson, Cathy, ....-; Wade, Daniel, ....- (Mylor : Ballistic)
The Art of Oddworld Inhabitants: The First Ten Years 1994 - 2004 is a high quality art book featuring the artistic journey of the legendary game company Oddworld Inhabitants from its first ten years - from Lorne Lanning's vision of the first Oddworld hero in 1994 to the present. The book is an extraordinarily high quality fine art production depicting the story of the art and vision of Oddworld and how the company approaches the art/design process. It also shows how the design process maintained the highest standards of creativity and quality while evolving a coherent universe populated with characters that expressed rich and unforgettable personalities .Filled with stunning examples of beautiful artwork including production design sketches, color roughs, storyboards, game screens and CG/FMV stills, The Art of Oddworld Inhabitants takes us through an incredible gallery of astonishing images. Finally, the book unveils Oddworld Inhabitants art that has never been seen before.
Keywords: Computergames